Second Street project hits downtown district - Wildermuth, Todd; Darden, Bill (Raton, NM Raton Range, 1997)
Article on the construction project for Raton's Second street .
Master List item # 3
File location is in the Raton File Cabinet
Keywords: Martinez, Vince; McQueary, Kathy; Apache Construction; Local History; Road Construction; Detours; Raton, New Mexico